THE NEED ANALYSIS OF ETHNOSCIENCE – BASED ENGLISH LEARNING MATERIAL: A CONTEXTUAL MODEL - Napiah Napiah (Universitas PGRI Semarang, 2022)
English is very important for students because English has become one of the International language used by many people. However some obstacles are usually faced by Indonesians who want to learn English. One of the causes of difficulties in learning English is that the material taught is not in accordance with the application of students' daily lives. Analyze the need for ethno science-based English material in contextual model in English subjects was the research purpose. Using the research instrument composed of questionnaire; data were gathered from seventy of the seventh grade students and three teachers of SMPN 14 Semarang to analyze the students and teachers’ needs in learning English. Descriptive statistics were used to analyzed the data. Based from the result, that students and teachers need interesting material in learning and teaching English subject. They agree of developing ethno science-based English material in contextual model because a English subjectis not only theory but need to practice it through student activities. The material better is if it is related to everyday life and the culture values of the local community